ASAS PEMBALIKAN BEBAN PEMBUKTIAN TINDAK PIDANA KORUPSI DALAM SISTEM PERADILAN PIDANA INDONESIA DAN MALAYSIA - Dermawan Tandeang (Dinamika, 2020)
ABSTRACTCorruption incurs economic losses with motives and modes of operation that are sophisticated and varied so that they are categorized as extraordinary crimes (Extra Ordinary Crime). To solve the problem, one of the efforts taken is by establishing the Reversal Burden. There are two fundamental questions that are the object of research, first: how to apply the principle of reversing the burden of proof as an effort to eradicate corruption against corruption in the Indonesian and Malaysian criminal justice systems. Second, what are the legal consequences arising from the imposition of burden of proof of corruption in the Indonesian and Malaysian criminal law systems. This study uses normative research with a historical approach, a comparative approach, and a legislative approach. This research shows that the principle of reversing the burden of proof of Indonesia in Article 12 B paragraph (1) letter a, Article 37 A, and Article 38 B of Law Number 31 of 1999 in conjunction with Law number 20 of 2001 is relative and Article 42 paragraph ( 1) and (2) Anti Corruption Act 1997 is absoluteKeywords: Reversal Burden of Proof, Corruption Crime, Indonesia and MalaysiaABSTRAKKorupsi menimbuklan kerugian ekonomi dengan motif dan modus operandi yang canggih dan variatif sehingga dikategorikan sebagai tindak pidana yang luar biasa (Extra Ordinary Crime). Untuk memecahkan masalah tersebut salah satu upaya yang ditempuh adalah dengan pengaturan Pembalikan Beban pembuktian. Terdapat dua pertanyaan mendasar yang menjadi objek penelitian, pertama: bagaimana penerapan asas pembalikan beban pembuktian sebagai upaya pemberantasan korupsi terhadap tindak pidana korupsi dalam sistem peradilan pidana Indonesia dan Malaysia. Kedua, apa akibat hukum yang timbul atas pemberlakuan beban pembuktian tindak pidana korupsi dalam sistem hukum pidana Indonesia dan Malaysia. Penelitian ini menggunakan penelitian normatif dengan pendekatan historis, pendekatan perbandingan, dan pendekatan perundang-undangan. Penelitian ini menunjukkan bahwa asas pembalikan beban pembuktian Indonesia dalam Pasal 12 B ayat (1) huruf a, Pasal 37 A, dan Pasal 38 B Undang-undang Nomor 31 tahun 1999 jo Undang-undang nomor 20 tahun 2001 bersifat relatif  dan Pasal 42 ayat (1) dan (2) Anti Corruption Act 1997 bersifat absolutKata Kunci : Pembalikan Beban Pembuktian, Tindak Pidana Korupsi, Indonesia dan Malaysia